Reclaiming Space: Postcolonial Ecocriticism in Toni Morrison’s ‘Sula’ - El Mitry, Abdelghani (International Journal of Linguistics and Translation Studies, 2024)
This article delves into the exploration of space in Toni Morrison’s novel Sula through the lens of postcolonial ecocriticism. Titled “Reclaiming Space: Postcolonial Ecocriticism in Toni Morrison’s Sula”, the article aims to analyze how the concept of space is portrayed in the novel, particularly in relation to themes of colonization, identity, and environmental degradation. By employing a postcolonial ecocritical perspective, the article seeks to uncover the ways in which the characters in Sula navigate and reclaim physical, social, and psychological spaces in the aftermath of colonialism. Key questions addressed in the article include: a). How does Morrison depict the relationship between space, power, and identity in Sula? b). In what ways do the characters in the novel challenge or conform to colonial structures through their interactions with space? c). How does the novel’s portrayal of the natural environment reflect broader themes of postcolonialism and ecological consciousness?